PENGARUH PROFITABILITAS, LIKUIDITAS, UKURAN PERUSAHAAN DAN LEVERAGE TERHADAP PERINGKAT OBLIGASI - Marwia Darma; Tina Sulistiyani (Universitas Ahmad Dahlan, 2019)
This study aims to determine the effect of profitability, liquidity, company size and leverage of the financial sector bond ratings in Indonesia Stock Exchange. The data in this research is secondary data obtained from www.idx.co.id. The total sample of 36 manufacturing sectors the company's bond period in 2017, using purposive sampling method. The analysis technique used is the logistic regression analysis and data processing using Eviews 9. The analysis showed that the positive effect on the profitability of bond ratings. liquidity positively affects bond ratings. Firm size positively affects bond ratings. Leverage negatively affect bond ratings. Companies should pay more attention and be able to increase the value of the company's liquidity so that companies ranked category of investment-grade bonds because investors are more interested in investing in bonds in the company investment-grade category.